Organizational responses to the COVID-19 pandemic in Victoria, Australia: A qualitative study across four healthcare settings - McGuinness, Sarah L.; Josphin, Johnson; Eades, Owen; Clifford, Sharon; Fisher, Jane; Kirkman, Maggie; Russell, Grant; Hodgson, Carol L.; Kelsall, Helen L.; Lane, Riki; Skouteris, Helen; Smith, Karen L.; et al. (Frontiers in Public Health, 2022)
Objective Organizational responses that support healthcare workers (HCWs) and mitigate health risks are necessary to offset the impact of the COVID-19 pandemic. We aimed to understand how HCWs and key personnel working in healthcare settings in Melbourne, Australia perceived their employing organizations' responses to the COVID-19 pandemic. Method In this qualitative study, conducted May-July 2021 as part of the longitudinal Coronavirus in Victorian Healthcare and Aged Care Workers (COVIC-HA) study, we purposively sampled and interviewed HCWs and key personnel from healthcare organizations across hospital, ambulance, aged care and primary care (general practice) settings. We also examined HCWs' free-text responses to a question about organizational resources and/or supports from the COVIC-HA Study's baseline survey. We thematically analyzed data using an iterative process. Results We analyzed data from interviews with 28 HCWs and 21 key personnel and free-text responses from 365 HCWs, yielding three major themes: navigating a changing and uncertain environment, maintaining service delivery during a pandemic, and meeting the safety and psychological needs of staff . HCWs valued organizational efforts to engage openly and honesty with staff, and proactive responses such as strategies to enhance workplace safety (e.g., personal protective equipment spotters). Suggestions for improvement identified in the themes included streamlined information processes, greater involvement of HCWs in decision-making, increased investment in staff wellbeing initiatives and sustainable approaches to strengthen the healthcare workforce. Conclusions This study provides in-depth insights into the challenges and successes of organizational responses across four healthcare settings in the uncertain environment of a pandemic. Future efforts to mitigate the impact of acute stressors on HCWs should include a strong focus on bidirectional communication, effective and realistic strategies to strengthen and sustain the healthcare workforce, and greater investment in flexible and meaningful psychological support and wellbeing initiatives for HCWs.